Analisis model pembelajaran pada buku teks Mardika Basa lan Sastra Jawa SMP/MTs Kelas VIII - Astuti, Puji Dian; Mujimin, Mujimin (Universitas Mulawarman, 2024)
This study aims to describe the syntax of the learning model based on learning activities in the textbook published by Erlangga entitled Mardika Basa lan Sastra Jawa SMP/MTs Kelas VIII. Descriptive qualitative was chosen as the method applied in this research with data sources from the textbook Mardika Basa lan Sastra Jawa SMP/MTs Kelas VIII. The type of instrument used is data card. The data was obtained by document review technique which was read repeatedly and then analyzed through content analysis. Data analysis was done by collecting data, reducing data, presenting data, and drawing conclusions. The results showed that the textbook Mardika Basa lan Sastra Jawa SMP/MTs Kelas VIII contains seven chapters of learning materials. There are five chapters (chapters 1, 3, 4, 5, and 7) that apply the Project Based Learning model. Based on these five chapters, it was found that the learning activities did not reflect syntax 3 (developing a schedule) and syntax 4 (monitoring students). In addition, the textbook contains some variations of learning activities that reflect the syntax of Project Based Learning.